MASALANING UMUMIY YECHIMIDAN XUSUSIY YECHIMGA O‘TISH - Zaxidova, M.A.; Giyasova, Z.R. (SCIENCE and SOCIETY, 2022)
In the article explaining the methodology for solving problems of studying the motion of a body moving under the influence of gravity, the ways of transition from the method of finding a general solution to a particular solution are shown and it is shown that the in formativeness of the problem can be increased by applying the method of graphical solution to these types of problems.